STAINED GLASS CRAFT MADE SIMPLE : Step-by-Step Instructions Using The Modern Copper-Foil Method - McDonell, James, author 632664 (NEW YORK : DOVER PUBLICATIONS, INC., 1985)
Includes bibliographical references (page 31).